Pemerintahan Jokowi-Jusuf Kalla Menurut Kacamata 5 Media Massa di Indonesia - Theresia D Wulandari (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2016)
Mass media has strong impact to public interest and has formed public perception on issues based on news they published. One of the most popular issues was one year period of Jokowi-Kalla presidential leadership in October 20, 2015. Evaluation, achievement, and reflection of both President and vice president who raise Nawacita program are assumed as indicators of success of them in leading Indonesia. Media objectivity in mass media is the main key in this research because objectivity is very important. The research used quantitative analysis by Robert Entman framing method. It was conducted by text analysis to editorial of five printed media, i.e: Jawa Pos, Kompas, Media Indonesia, Republika, and Tempo, published at October 20, 2015. The research also employs interview and observe secondary sources to as a part of contectual analysis. The result shows objectivity and imparsiality of five printed media in Indonesia in covering Jokowi and Jusuf Kalla presidential leadership. It is shown how media preserve Jokowi-Kalla performance in their 1st year governance as news object.